Toward Personalized Medicine: Using Cardiomyocytes Differentiated From Urine‐Derived Pluripotent Stem Cells to Recapitulate Electrophysiological Characteristics of Type 2 Long QT Syndrome. Issue 9 (September 2015) - Jouni, Mariam; Si‐Tayeb, Karim; Es‐Salah‐Lamoureux, Zeineb; Latypova, Xenia; Champon, Benoite; Caillaud, Amandine; Rungoat, Anais; Charpentier, Flavien; Loussouarn, Gildas; Baró, Isabelle; Zibara, Kazem; Lemarchand, Patricia; et al.
Abstract : Background: Human genetically inherited cardiac diseases have been studied mainly in heterologous systems or animal models, independent of patients' genetic backgrounds. Because sources of human cardiomyocytes (CMs) are extremely limited, the use of urine samples to generate induced pluripotent stem cell–derived CMs would be a noninvasive method to identify cardiac dysfunctions that lead to pathologies within patients' specific genetic backgrounds. The objective was to validate the use of CMs differentiated from urine‐derived human induced pluripotent stem (UhiPS) cells as a new cellular model for studying patients' specific arrhythmia mechanisms. Methods and Results: Cells obtained from urine samples of a patient with long QT syndrome who harbored the HERG A561P gene mutation and his asymptomatic noncarrier mother were reprogrammed using the episomal‐based method. UhiPS cells were then differentiated into CMs using the matrix sandwich method. UhiPS‐CMs showed proper expression of atrial and ventricular myofilament proteins and ion channels. They were electrically functional, with nodal‐, atrial‐ and ventricular‐like action potentials recorded using high‐throughput optical and patch‐clamp techniques. Comparison of HERG expression from the patient's UhiPS‐CMs to the mother's UhiPS‐CMs showed that the mutation led to a trafficking defect that resulted in reduced delayed rectifier K + current (IKr ). This phenotype gave rise to action potential prolongation and arrhythmias. Conclusions: UhiPS cells from patients carrying ion channel mutations can be used as novel tools to differentiate functional CMs that recapitulate cardiac arrhythmia phenotypes.